A heteroelectrode structure for solar water splitting: integrated cobalt ditelluride across a TiO2-passivated silicon microwire array. Issue 7 (17th February 2017) - Bazri, Behrouz; Lin, Yu-Chen; Lu, Tzu-Hsiang; Chen, Chih-Jung; Kowsari, Elaheh; Hu, Shu-Fen; Liu, Ru-Shi
Abstract : CoTe2 @TiO2 -Si-MWs provide active sites for proton reduction and combine surface hydrogen atoms into molecular hydrogen. Abstract : Cobalt ditelluride as a cocatalyst on the surface of a silicon microwire array (Si-MWs) and as a heterocathode structure for the hydrogen evolution reaction was synthesized via a one-step drop-casting method. The improvement in the photo-electrocatalytic efficiency, including the 0.66 V anodic shift in the onset potential and the −24.0 mA cm −2 photocurrent density, is comparable to that of other cocatalyst systems for water reduction. The photocurrent decay of CoTe2 @Si-MWs further improved to roughly −10 mA cm −2 by deposition of 10 nm atomic-layer-deposited TiO2 on the Si-MW photocathode for 67 min. Outcomes of this study may demonstrate the possibility of introducing a new class of telluride cocatalyst heterocathode system as an alternative to noble metals in facilitating the water splitting reaction. The cobalt ditelluride across the TiO2 -passivated Si-MWs heterocathode is reported to have an effective response to solar water reduction for the first time.